Why Does Running an Electronic Journal Need Any Money? - Michael Scriven (The Evaluation Center at Western Michigan University, 2007)
Comment on the following quotation from the latest issue (9/07) of a fairly new (1995) journal, Sociological Research Online published in the UK.